2017
DOI: 10.1002/hed.24762
|View full text |Cite
|
Sign up to set email alerts
|

Unknown primary head and neck squamous cell carcinoma in the era of fluorodeoxyglucose‐positron emission tomography/CT and intensity‐modulated radiotherapy

Abstract: Locoregional outcome of head and neck CUP managed with modern techniques is good. Future research needs to focus on reducing toxicity and patients prone for distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Salvage therapy consisted in radiotherapy (two patients), surgery (two patients), surgery plus postoperative radiotherapy (two patients), chemotherapy or targeted therapy with palliative intent ( four patients). All patients died of their disease within a median time of 9.8 months after salvage therapy, eight due to distant metastases and two due to local evolution and fatal carotid hemorrhage. The regional control rate was 83% in the UL‐RT group and 72% in the COMP RT ( P = .39).…”
Section: Resultsmentioning
confidence: 99%
“…Salvage therapy consisted in radiotherapy (two patients), surgery (two patients), surgery plus postoperative radiotherapy (two patients), chemotherapy or targeted therapy with palliative intent ( four patients). All patients died of their disease within a median time of 9.8 months after salvage therapy, eight due to distant metastases and two due to local evolution and fatal carotid hemorrhage. The regional control rate was 83% in the UL‐RT group and 72% in the COMP RT ( P = .39).…”
Section: Resultsmentioning
confidence: 99%
“…Although this is the first study to compare a CUP cohort with a matched OPX cohort, other studies suggest that CUP patients have excellent outcomes. Table demonstrates previous studies on CUP and reports outcomes for all patients regardless of HPV status . Most studies are heterogeneous and include patients with unknown HPV status or HPV‐negative disease and then later stratify by HPV status.…”
Section: Discussionmentioning
confidence: 99%
“…Table II demonstrates previous studies on CUP and reports outcomes for all patients regardless of HPV status. [17][18][19][20][21][22][23][24] Most studies are heterogeneous and include patients with unknown HPV status or HPV-negative disease and then later stratify by HPV status. A direct comparison between HPV-associated CUP and HPV-associated OPX outcomes has stronger implications when considering future inclusion criteria for clinical investigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…82 In the overall population, long survivals are achieved with both cisplatin dose levels. 84 Similarly, another study of 260 patients with SCCUP (90 HPV-related SCCUP) treating nasopharyngeal and oropharyngeal mucosa showed high rates of disease control and survival. 82 Mucosal irradiation was a common practice in the past but the larynx and hypopharynx are currently spared because recurrences are rare at these sites.…”
Section: Radiation With or Without Concomitant Chemotherapymentioning
confidence: 97%
“…71,83 In one study of 80 patients with SCCUP (18 HPV-related SCCUP), 75 patients underwent elective RT (46 Gy in 2 Gy/fraction) of the full upper aerodigestive mucosa with none experiencing local recurrence. 84 Similarly, another study of 260 patients with SCCUP (90 HPV-related SCCUP) treating nasopharyngeal and oropharyngeal mucosa showed high rates of disease control and survival. 71 However, contrary to radiating large volumes of the pharyngeal axis (the more common approach), an Australian study suggested that unilateral RT might be a reasonable approach in some good prognosis patients (those who did not have parotid or isolated level IV or V nodal involvement) with p16/HPVpositive SCCUP.…”
Section: Radiation With or Without Concomitant Chemotherapymentioning
confidence: 97%